Wm & H'ry : literature, love, and the letters between William and Henry James - Hallman, J. C. (University of Iowa Press, 2013)
Readers generally know only one of the two famous James brothers. Literary types know Henry James; psychologists, philosophers, and religion scholars know William James. In reality, the brothers' minds were inseparable, as the more than eight hundred letters they wrote to each other reveal. In this book, the author mines the letters for mutual affection and influence, painting a moving portrait of a relationship between two extraordinary men.